Dimerization in LBD16 and LBD18 Transcription Factors Is Critical for Lateral Root Formation. Issue 1 (23rd March 2017) - Lee, Han Woo; Kang, Na Young; Pandey, Shashank K.; Cho, Chuloh; Lee, Sung Haeng; Kim, Jungmook
Abstract : The leucine-zipper-like coiled-coil motif is crucial for the homodimerization of LBD16 and LBD18 and for the transcriptional regulation and biological function in Arabidopsis. Abstract: LATERAL ORGAN BOUNDARIES DOMAIN/ASYMMETRIC LEAVES2-LIKEs (hereafter referred to as LBD) are plant-specific transcription factors that play important roles in a plethora of plant growth and development. The leucine (Leu) zipper-like coiled-coil motif in the lateral organ boundaries domain of the class I LBD proteins has been proposed to mediate protein dimerization, but it has not been experimentally assessed yet. LBD16 and LBD18 have been well characterized to play important roles in lateral root development in Arabidopsis ( Arabidopsis thaliana ). Here, we investigated the role of the coiled-coil motif in the dimerization of LBD16 and LBD18 and in transcriptional regulation and biological function. We built the molecular models of the coiled coil of LBD16 and LBD18, providing the probable Leu zipper models of the helix dimer. Using a variety of molecular techniques, such as bimolecular fluorescence complementation, luciferase complementation imaging, GST pull down, and coimmunoprecipitation assays, we showed that the conserved Leu or valine residues in the coiled-coil motif are critical for the dimerization of LBD16 or LBD18. Using transgenic Arabidopsis plants that overexpress HA:LBD16 or HA:LBD16 Q in lbd16 or HA:LBD18 or HA:LBD18 Q in lbd18, we demonstrated that the homodimerization of LBD18 mediated by the coiled-coil motif is crucial for transcriptional regulation via promoter binding and for lateral root formation. In addition, we found that the carboxyl-terminal region beyond the coiled-coil motif in LBD18 acts as an additional dimerization domain. These results provide a molecular basis for homodimerization and heterodimerization among the 42 Arabidopsis LBD family members for displaying their biological functions.